2005
DOI: 10.1021/ja0437508
|View full text |Cite
|
Sign up to set email alerts
|

Time−Temperature Superposition for Viscoelastic Properties of Regioregular Poly(3-hexylthiophene) Films

Abstract: Shear moduli were determined for chemically polymerized and solvent cast regioregular poly(3-hexylthiophene) films, using thickness shear mode acoustic wave resonators. The results are strikingly different to those for electropolymerized regiorandom poly(3-hexylthiophene) films. The time scale of the measurement was varied directly by use of higher harmonics of the acoustic wave resonator and indirectly via temperature. The significant variations in shear modulus with effective time scale can be "normalized"on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(55 citation statements)
references
References 32 publications
2
53
0
Order By: Relevance
“…As Figure 8-Route I shows, the PPy-DS film undergoes successive swelling and shrinking cycles during the redox process. In addition, a dehydration process of cations for freshly prepared films has been reported during anodic potential sweep due to the lower porosity of PPy-DS film in a relatively shrunken state [38]. As for route II which is explored in this work, the volumetric change capability of the film can become poorer upon cycling, and the solvation shell of cation at -0.6 V is removed during the cycling process.…”
Section: Viscoelastic Property Changes Upon Film Agingmentioning
confidence: 93%
See 2 more Smart Citations
“…As Figure 8-Route I shows, the PPy-DS film undergoes successive swelling and shrinking cycles during the redox process. In addition, a dehydration process of cations for freshly prepared films has been reported during anodic potential sweep due to the lower porosity of PPy-DS film in a relatively shrunken state [38]. As for route II which is explored in this work, the volumetric change capability of the film can become poorer upon cycling, and the solvation shell of cation at -0.6 V is removed during the cycling process.…”
Section: Viscoelastic Property Changes Upon Film Agingmentioning
confidence: 93%
“…The real component (G´) describes the energy storage capability of the polymer chains and the imaginary part (G") is associated with the energy dissipation of the film due to irreversible deformation of polymer chains [38] .…”
Section: Electroacoustic Impedance Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…This work has shown that the QCM provides the opportunity to detect viscoelastic properties of the deposited layer. Several studies have been conducted by Hillman and co-workers on polythiophene [4][5][6][7][8][9][10][11][12][13] . Their work had been carried out using a QCM device working with an impedance system.…”
Section: Introductionmentioning
confidence: 99%
“…The value of its acoustic resistance should be taken at main resonance. It is defined by losses and storage moduli of the film, which may be solvated depending on applied potential [15] in case of redox polymers. It also depends on the surface roughness of interface with liquid [16].…”
mentioning
confidence: 99%